Uniportal subxiphoid bilateral removal of self-introduced thoracic foreign bodies. Issue 4 (6th April 2020) - Sahdev, Nikhil; Punjabi, Karan; Williams, Luke; Peryt, Adam; Coonar, Aman; Aresu, Giuseppe
Abstract: This is a report of a 31-year-old male refugee, who was admitted to Intensive Therapy Unit after being found in severe chest pain after escaping extreme torture from his home country. He was found to have four nails in his thorax. These were removed using a subxiphoid video-assisted thorascopic surgery (VATS) technique. This technique allowed excellent visualization of the right, left and anterior mediastinal part of the chest and therefore preventing damage or injury to surrounding structures. This was particularly useful in a complex case such as this. By avoiding an intercoastal incision and intercostal manipulation, our patient had limited pain post-procedure facilitating an earlier aggressive mobilization program with potential benefit in terms of improved lung expansion, reduction of atelectasis and lung infections. With the right training, the technical challenges of using the technique should be overcome and thus the benefits of subxiphoid VATS will be offered to a larger portion of thoracic surgical patients.